Neural regions underlying object and action naming: complementary evidence from acute stroke and primary progressive aphasia. Issue 6 (3rd June 2022) - Breining, Bonnie L.; Faria, Andreia V.; Caffo, Brian; Meier, Erin L.; Sheppard, Shannon M.; Sebastian, Rajani; Tippett, Donna C.; Hillis, Argye E.
ABSTRACT: Background: Naming impairment is commonly noted in individuals with aphasia. However, object naming receives more attention than action naming. Furthermore, most studies include participants with aphasia due to only one aetiology, commonly stroke. We developed a new assessment, the Hopkins Action Naming Assessment (HANA), to evaluate action naming impairments. Aims: Our aims were to show that the HANA is a useful tool that can (1) identify action naming impairments and (2) be used to investigate the neural substrates underlying naming. We paired the HANA with the Boston Naming Test (BNT) to compare action and object naming. We considered participants with aphasia due to primary progressive aphasia (PPA) or acute left hemisphere stroke to provide a more comprehensive picture of brain–behaviour relationships critical for naming. Behaviourally, we hypothesised that there would be a double dissociation between object and action naming performance. Neuroanatomically, we hypothesised that different neural substrates would be implicated in object vs. action naming and that different lesion-deficit associations would be identified in participants with PPA vs. acute stroke. Methods & Procedures: Participants (N = 138 PPA, N = 37 acute stroke) completed the BNT and HANA. Behavioural performance was compared. A subset of participants (N = 31 PPA, N = 37 acute stroke) provided neuroimaging data. The whole brain was automatically segmented into regions of interest (ROIs). For participants with PPA, the image variables were the ROI volumes, normalised by brain volume. For participants with acute stroke, the image variables were the percentage of each ROI that was lesioned. The relationship between ROIs likely to be involved in naming performance was modelled with LASSO regression. Outcomes & Results: Behavioural results showed a double dissociation in performance: in each group, some participants displayed intact performance relative to healthy controls on actions but not objects and/or significantly better performance on actions than objects, while others showed the opposite pattern. These results support the need to assess both objects and actions when evaluating naming deficits. Neuroimaging results identified different regions associated with object vs. action naming, implicating overlapping but distinct networks of regions. Furthermore, results differed for participants with PPA vs. acute stroke, indicating that critical information may be missed when only one aetiology is considered. Conclusions: Overall, the study provides a more comprehensive picture of the neural bases of naming, underscoring the importance of assessing both objects and actions and considering different aetiologies of damage. It demonstrates the HANA's utility.